Mapping fusogenicity of ciprofloxacin-loaded liposomes with bacterial cells - Patil, Runali; Torris, Arun; Bhat, Suresh; Patil, Sharvil (AAPS Pharmscitech, 2019)
The process of liposome fusion with cellular membrane plays key role in delivering encapsulated drug molecule into the cell. This process becomes very important for molecules having low permeability as they fail to reach the site of action located inside the cell. Ciprofloxacin (CIP), a broad-spectrum BCS class IV antibiotic, has poor permeability. In the present work, CIP-loaded liposomes were prepared using solvent evaporation method and optimized by 3(2) factorial design approach. The optimized batch of CIP-loaded liposomes was characterized for size, entrapment efficiency, zeta potential, FTIR, and microbial susceptibility study on Staphylococcus aureus (gram-positive bacteria) and Escherichia coli (gram-negative bacteria). Confocal microscopy was used to study the fusogenicity process of CIP-loaded liposomes with bacterial cells. Additionally, the kinetics of fusogenicity process was studied using SAXS for the first time. Surprisingly, the rate of fusion of CIP-loaded liposomes with cell wall of S. aureus was twice when compared to the cell wall of E. coli. It is believed that the current work can act as a roadmap in selection of proper excipients while developing formulations which would expedite the fusogenicity and may execute pharmacological activity of poorly penetrable drug molecules at lower dose.
Keywords: ciprofloxacin; confocal microscopy; fusion; liposomes; SAXS